Encapsulation of endoglucanase using a biopolymer Gum arabic for its controlled release - Ramakrishnan, Anish; Pandit, Nilesh; Badgujar, Mahesh; Bhaskar, C.; Rao, Mala (Bioresource Technology, 2007)
{Gum Arabic, a biodegradable natural polymer was used as a matrix to encapsulate endoglucanase from Thermomonospora sp. The modified enzyme retained complete biocatalytic activity and exhibited a shift in the optimum temperature [
Keywords: Enzyme catalysis; OPTA; Thermomonospora sp.; Xylanase